Ce qu’apportent les interactions verbales à l’acquisition de l’orthographe grammaticale - Danièle Cogis (Recherches en Éducation)
Persistent errors in spelling are usually explained by a failure to apply the rules. But by the 1990s, research using the methodology of the metagraphic interviews showed that the acquisition process was based on a progressive conceptualisation of grammatical concepts. It is therefore important to work out the discrepancy between the conceptual elaboration of students who are confronted with a very complex orthographic system and the parameters that govern linguistic functioning. The article focuses on the relationship between verbalisation and conceptualisation in an interview with two grade 4 students and highlights the path that led them to “discovery” past participles used as adjectives.